PENGEMBANGAN DESAIN PEMBELAJARAN BERBASIS PROBLEM POSING DALAM UPAYA MENINGKATKAN KEMAMPUAN PENALARAN KONSEP LINGKARAN PADA SISWA SMP KELAS VIII - Farman Farman; Yusryanto Yusryanto (Universitas Muhammadiyah Semarang, 2018)
This research aims to obtain a valid, practical, and effective instructional design of circle material for grade VIII of SMP-TQ Muadz Bin Jabal Kendari. Instructional design has developed based on Isman model (2011). To develop a design, learning devices and instruments were developed. The prototype were validated and the test showed by the average of validity value. The practicality was shown by the average percentage of achievement from the observation of teacher activity. The analysis result of the effectiveness of the design is measured based on the average of achievement from the observation of student activity, the average of circle reasoning ability and the average of the percentage of achievement of student responses questionnaire. Based on the finding, it can be concluded that the instructional design of circle material with Isman model for grade VIII of SMP-TQ Muadz Bin Jabal Kendari were valid, practice, and effective.